Cohort study of outpatient hemodialysis management strategies for COVID-19 in North-West London (2020)
Background: Dialysis patients are at risk of severe COVID-19. We managed COVID-19 haemodialysis outpatients in dedicated satellite dialysis units. This provided rare opportunity to study early disease progress in communitybased patients. We aimed to (1) understand COVID-19 progression, (2) identify markers of future clinical severity and (3) assess associations between dialysis management strategies and COVID-19 clinical outcomes. Methods: We conducted a cohort study of all outpatients managed at a COVID-19 haemodialysis unit. We analysed data recorded as part of providing COVID-19 clinical care. We analysed associations between features at diagnosis and the first 3 consecutive haemodialysis sessions in patients who required future hospital admission, and those who had died at 28 days. Results: Isolated outpatient haemodialysis was provided to 106 patients over 8 weeks. No patients received antiviral medication or hydroxychloroquine. 21 patients (20%) were admitted at COVID-19 diagnosis. 29 of 85 patients (34%) were admitted after initial outpatient management. 16 patients (15%) died. By multivariate analysis, non-active transplant list status, use of institutional transport, and increased white cell count associated with future hospitalisation and increased age associated with death. Oxygen saturations progressively decreased over the first 3 dialysis sessions in the cohorts who progressed to future hospital admission or death. Mean ultrafiltration volume of the first three haemodialysis sessions was reduced in the same cohorts. Conclusions: Outpatient haemodialysis in patients with COVID-19 is safe for patients and staff. Features at the first 3 dialysis sessions can identify individuals at risk of future hospitalisation and death from COVID-19.